FEMALE AS OWNER AND MANAGER, EXPORT ORIENTATION, AND VALUE RELEVANCE OF INNOVATION EVIDENCE FROM EMERGIN G COUNTRIES - Ullah, Dr. Hamid; Shah, Dr. Hamid Ali; Khan, Dr Sajjad Ahmad (The journal of contemporary issues in business and government, 2021)
The study investigates the impact of the females at the top, females with majority and minority ownership, and females as workers on the export orientation. Moreover, the study also examines the value relevance of the product, process, market, and organizational innovation in the relationship between the females at four different levels in hierarchy and export orientations in the case of emerging markets. The study use data of Enterprise survey conducted by the World Bank from 2002 to 2019 for 40 emerging countries. The sample included 20,019 export- oriented firms. We use hierarchical regression models for estimation. The results of various models show that females at the top position and females with majority ownership have a positive and significant effect on the export orientation. However, female minority ownership and female workers have no significant influence on export orientation. Moreover, product, market, and process innovations have a positive and significant incremental effect in the relationship between females at the top and females holding majority ownership and export orientation. The theory of internationalization is found valid as females in the two significant positions (majority shareholdings and manager at top) are found relevant to the export orientation of the firms. The findings of the study that females as controlling shareholder behave differently than men in emerging markets challenge the principal-principal agency conflicts. Organizations chasing the goal to improve their revenues and grow through exports shall try to attract female investors and hire or promote female to the rank of top-level managerial positions.Moreover, the results of the study encourage small firms to employ and utilize the potentials of females as managers and focus on innovations to exploit export opportunities.Whereas, to boost exports of the local industries, governments are required to provide structural and legal support.